Propriety and Rule of Alevism in the Ashik Kul Semai’s Works - Gedik, Seda (Journal of Alevism-Bektashism Studies, 2019)
The upbringing of ashiks, belief system they belong to and the context in which they performed poems, have influenced the content of their poems. The influences of upbringing are also clearly seen in the poetry of Ashik Kul Semai, who was brought up within Alevi belief system and “zakirlik” tradition. By expressing his commitment and love for Muhammad-Ali, Twelve Imams and Ehlibeyt in his poems, Ashik Kul Semai, who participated in “cem” ceremonies as a child and had opportunity to learn Alevism through experience and in theory, emphasized in his poetry the importance of propriety (edep) and rule (erkan) which aspirants belonging to Alevi tradition have to hold to.According to Alevi belief, there are certain norms and specific stages which the person who enters “the right path” needs to hold to and pass through. These stages and norms are called “edep” (propriety) and “erkan” (rule). In order to become perfect human being and reach God, aspirant needs to pass through these stages: to get connected to a mentor/guide, to know yourself, self-denial and four-graded forty maqam. Therefore, Ashik Kul Semai, member of Alevi-Bektashi tradition, emphasized the propriety and rule in Alevism in his poems. According to Alevi belief, aspirant must pass through four-graded forty maqam to reach and commune with God. Furthermore, four-graded forty maqam that specifies stages which aspirant must pass through, is a sine qua non for reaching the stage of becoming perfect human being.Semai expressed in his poems that there are stages of four-grated forty maqam, called sharia, tariqa, marifa and haqiqa, which aspirant has to pass through on “the right path” and that only the aspirant who passes properly through this stages can advance on the path of God. Furthermore, Semai emphasized that the aspirant who enters “the right path” and risks everything for this purpose, can become a perfect human being only by passing though these stages. According to Alevi belief, humans can reach God’s secret only when they become a perfect human being. Therefore, it is highly important in Alevi belief system to pass through four-grated forty maqam.
Keywords: Alevism; propriety; rule; Ashik Kul Semai; aspirant